JALAN SEHAT SEBAGAI MEDIA PROMOSI POSYANDU UNTUK MENINGKATKAN PARTISIPASI KESEHATAN IBU DAN ANAK DI DESA MARGA MULYA - Ladyka Viola Aulia Armawan; Althyah Dwi Ghina; ⁠Anggun Kesuma; Annisa Fitri; Ayu Nastiti Maharani; Dwi Utami; ⁠Lia Afridah; Ersi Prima Putri; ⁠Marsha Cahya Nadira Adham; Mila Jovita Putri; Nuril Fijriah; Rahmah Fadhilah Husna; ⁠Rivandeska Armando (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2026)
Low community participation in Posyandu remains a challenge in improving maternal and child health in Marga Mulya Village. The contributing factors include low education levels, farming occupations, inflexible Posyandu schedules, and unhealthy household expenditures such as smoking. The Field Learning Experience (PBL) activity of Group 4 introduced the “SEHATI” (Healthy and Active Together with the Residents of Marga Mulya Village) program, which involves a healthy walking activity as a non-formal educational medium to raise awareness about the importance of Posyandu. This activity involves mothers of infants and heads of households, combined with health education sessions, distribution of pamphlets, and door prizes. Evaluation results showed an increase in the number of infant Posyandu visits from 40 to 48 children, or a 20% increase after the activity was implemented. Additionally, the enthusiasm of the community during the activity served as an indicator of increased attention to health services. Community-based health promotion strategies that are enjoyable and participatory have proven effective in raising community awareness and encouraging behavioral change. This activity is expected to serve as a model for community-based approaches to address low Posyandu participation, particularly in rural areas.